SMART Stone Multidisciplinary Team (MDT) and patient care: recommendations for the adult high-risk kidney stone patient pathway - Somani, Bhaskar; Emiliani, Esteban; Knoll, Thomas; Mandrile, Giorgia; Rumsby, Gill; Acquaviva, Cecile; Bhojani, Naeem; Bin Hamri, Saeed; Bres-Niewada, Ewa; Davis, Niall F.; Fuster, Daniel G.; Garrelfs, Sander F.; et al. (World journal of urology, 2025)
Purpose The SMART Stone Multidisciplinary Team (MDT) recommendations aim to provide guidance on the role of the MDT in the early identification, referral and assessment of adult high-risk recurrent kidney stone formers to advance patient care. Methods Recommendations were developed by the expert Steering Committee (SC) comprising of three Urologists, one Nephrologist, and two Biochemists/Geneticists from the UK, Spain, Germany, and Italy. These recommendations were voted on by invited specialists via an online survey to determine their level of agreement, from ‘strongly agree’ to ‘strongly disagree’. With an agreement threshold set at ≥ 70%, the SC reviewed the survey results, additional comments, and any areas of disagreement before finalizing the recommendations. Results A total of 44 recommendations were developed by the SC designed to support the set-up of an ideal MDT. Thirteen core recommendations were chosen as being highest priority and were voted on by 29 invited specialists from 19 countries across Europe, Canada, East Asia, South/Southeast Asia, and the Middle East. All 13 core recommendations reached the ≥ 70% agreement threshold. The remaining 31 recommendations were voted on by those specialists who opted-in to partake in the extended questionnaire. Fifteen specialists provided their responses from 14 different countries. All 31 recommendations reached the ≥ 70% agreement threshold. Conclusions An ideal MDT process can achieve comprehensive, high-quality, and coordinated patient care, which is especially useful for patients with complex stone diseases. A high level of agreement was reached in areas relating to the implementation of an ideal MDT in identifying high-risk stone formers.
Online veröffentlicht: 22. April 2025
Gesehen am 26.06.2025